The interplay between genetic background and sexual dimorphism of doxorubicin-induced cardiotoxicity. Issue 1 (December 2016) - Zordoky, Beshay; Radin, M.; Heller, Lois; Tobias, Anthony; Matise, Ilze; Apple, Fred; McCune, Sylvia; Sharkey, Leslie
Abstract Background Doxorubicin (DOX) is a very effective anticancer medication that is commonly used to treat hematological malignancies and solid tumors. Nevertheless, DOX is known to have cardiotoxic effects that may lead to cardiac dysfunction and failure. In experimental studies, female animals have been shown to be protected against DOX-induced cardiotoxicity; however, the evidence of this sexual dimorphism is inconclusive in clinical studies. Therefore, we sought to investigate whether genetic background could influence the sexual dimorphism of DOX-induced cardiotoxicity. Methods Male and female Wistar Kyoto (WKY) and Spontaneous Hypertensive Heart Failure (SHHF) rats were used. DOX was administered in eight doses of 2 mg/kg/week and the rats were followed for an additional 12 weeks. Cardiac function was assessed by trans-thoracic echocardiography, systolic blood pressure was measured by the tail cuff method, and heart and kidney tissues were collected for histopathology. Results Female sex protected against DOX-induced weight loss and increase in blood pressure in the WKY rats, whereas it protected against DOX-induced cardiac dysfunction and the elevation of cardiac troponin in SHHF rats. In both strains, female sex was protective against DOX-induced nephrotoxicity. There was a strong correlation between DOX-induced renal pathology and DOX-induced cardiac dysfunction. Conclusions This study highlights the importance of studying the interaction between sex and genetic background to determine the risk of DOX-induced cardiotoxicity. In addition, our findings suggest that DOX-induced nephrotoxicity may play a role in DOX-induced cardiac dysfunction in rodent models.